1997
DOI: 10.1210/mend.11.6.0007
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids, Eicosanoids, and Hypolipidemic Agents Identified as Ligands of Peroxisome Proliferator-Activated Receptors by Coactivator-Dependent Receptor Ligand Assay

Abstract: Peroxisome proliferator-activated receptors (PPARs) are nuclear hormone receptors controlling the expression of genes involved in lipid homeostasis. PPARs activate gene transcription in response to a variety of compounds including hypolipidemic drugs as well as natural fatty acids. From the plethora of PPAR activators, Scatchard analysis of receptor-ligand interactions has thus far identified only four ligands. These are the chemotactic agent leukotriene B4 and the hypolipidemic drug Wy 14,643 for the alpha-su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
280
4
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 882 publications
(299 citation statements)
references
References 30 publications
13
280
4
2
Order By: Relevance
“…This specificity may derive from various lipase-specific properties: different substrates (triglyceride vs. phospholipids, saturated vs. unsaturated FA), subsequent FA modifications, and͞or the lipolytic products generated. Regardless, these results argue against the assumption based on prior in vitro data that FA in general activate PPARs (38)(39)(40) or that FA generation by any means of lipolysis would do the same. Rather, our findings suggest different transcriptional responses dependent on the specific mechanism of FA generation and uptake (Fig.…”
Section: Discussioncontrasting
confidence: 63%
“…This specificity may derive from various lipase-specific properties: different substrates (triglyceride vs. phospholipids, saturated vs. unsaturated FA), subsequent FA modifications, and͞or the lipolytic products generated. Regardless, these results argue against the assumption based on prior in vitro data that FA in general activate PPARs (38)(39)(40) or that FA generation by any means of lipolysis would do the same. Rather, our findings suggest different transcriptional responses dependent on the specific mechanism of FA generation and uptake (Fig.…”
Section: Discussioncontrasting
confidence: 63%
“…Future studies should be performed to compare strategies with the wild-type and mutant systems. To date, several in vitro assays have been developed for screening ER ligands by using either purified ER␣ protein or ER isolated from cell lysates (18)(19)(20)(21). Limited fluorescence-based assays (22) have been developed to measure receptor conformational changes (23) and recruitment of coactivator peptides (22,24,25) in the full-length hER␣ within cell culture (26).…”
Section: Discussionmentioning
confidence: 99%
“…The biological effects of 15d-PGJ 2 have attracted considerable interest in recent years. It was initially identified as a high affinity natural ligand for the peroxisome proliferator-activated receptor-␥ (PPAR␥) and shown to exert several effects through binding to this nuclear receptor (2)(3)(4)(5). More recently, several recent studies have shown that 15d-PGJ 2 exhibits a potent anti-inflammatory effect by attenuating the expression of proinflammatory mediators in activated monocytes/macrophages mainly through the inhibition of NF-B-dependent transcription of inflammatory genes (6,7).…”
Section: -mentioning
confidence: 99%